2021
DOI: 10.1002/ana.26235
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cardiopulmonary Bypass on Neurogenesis and Cortical Maturation

Abstract: Objective: Neurodevelopmental delays and frontal lobe cortical dysmaturation are widespread among children with congenital heart disease (CHD). The subventricular zone (SVZ) is the largest pool of neural stem/progenitor cells in the postnatal brain. Our aim is to determine the effects of cardiopulmonary bypass (CPB) on neurogenesis and cortical maturation in piglets whose SVZ development is similar to human infants. Methods: Three-week-old piglets (n = 29) were randomly assigned to control (no surgery), mild-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…Our structural imaging analyses demonstrated differences in the volume of frontal cortices among the 3 groups ( Supplemental Figure 12B ), consistent with MSC-induced inhibition of neuronal apoptosis. Similar to our previous studies, 6 the gyrification index was lower after CPB compared to controls ( Figures 5A and 5B ). Notably, CPB-induced alterations of gyrification were improved in the brain with BM-MSC treatment ( Figures 5A and 5B ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Our structural imaging analyses demonstrated differences in the volume of frontal cortices among the 3 groups ( Supplemental Figure 12B ), consistent with MSC-induced inhibition of neuronal apoptosis. Similar to our previous studies, 6 the gyrification index was lower after CPB compared to controls ( Figures 5A and 5B ). Notably, CPB-induced alterations of gyrification were improved in the brain with BM-MSC treatment ( Figures 5A and 5B ).…”
Section: Resultssupporting
confidence: 91%
“… 4 Our previous studies found prolonged microglia expansion and cortical dysmaturation after cardiopulmonary bypass (CPB). 5 , 6 Newly acquired brain damage is commonly recognized after surgery with current technologies. 7 , 8 Thus, further refinement of pediatric cardiac surgery will likely assist in the improvement of neurodevelopmental outcomes in CHD.…”
mentioning
confidence: 99%